Quadrivalent Human Papillomavirus (HPV) Vaccine Induces HPV-Specific Antibodies in the Oral Cavity: Results From the Mid-Adult Male Vaccine Trial. (10th August 2016) - Pinto, Ligia A.; Kemp, Troy J.; Torres, B. Nelson; Isaacs-Soriano, Kimberly; Ingles, Donna; Abrahamsen, Martha; Pan, Yuanji; Lazcano-Ponce, Eduardo; Salmeron, Jorge; Giuliano, Anna R.
Abstract: Background.  Human papillomavirus virus type 16 (HPV-16) and HPV-18 cause a large proportion of oropharyngeal cancers, which are increasing in incidence among males, and vaccine efficacy against oral HPV infections in men has not been previously evaluated. Methods.  Sera and saliva collected in mouthwash and Merocel sponges at day 1 and month 7 were obtained from 150 men aged 27–45 years from Tampa, Florida, and Cuernavaca, Mexico, who received Gardasil at day 1 and months 2 and 6. Specimens were tested for anti–HPV-16 and anti–HPV-18 immunoglobulin G (IgG) levels by an L1 virus-like particle–based enzyme-linked immunosorbent assay. Results.  All participants developed detectable serum anti–HPV-16 and anti–HPV-18 antibodies, and most had detectable antibodies in both oral specimen types at month 7 (HPV-16 was detected in 93.2% of mouthwash specimens and 95.7% of sponge specimens; HPV-18 was detected in 72.1% and 65.5%, respectively). Antibody concentrations in saliva were approximately 3 logs lower than in serum. HPV-16– and HPV-18–specific antibody levels, normalized to total IgG levels, in both oral specimen types at month 7 were significantly correlated with serum levels (for HPV-16, ρ was 0.90 for mouthwash specimens and 0.92 for sponge specimens; for HPV-18, ρ was 0.89 and 0.86, respectively). Conclusions.  This is the first study demonstrating that vaccination of males with Gardasil induces HPV antibody levels at the oral cavity that correlate with circulating levels.